2007
DOI: 10.1038/sj.ki.5002039
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated expression of senescence associated cell cycle inhibitor p16INK4A in kidneys with glomerular disease

Abstract: The cell cycle inhibitor p16(INK4A) (also known as cyclin-dependent kinase inhibitor 2A) is expressed in vivo in many tissues with age. The exposure of certain chronic stresses can trigger p16(INK4A) expression and a senescence-like phenotype. We studied whether p16(INK4A) expression is induced in glomerular disease (GD). We performed p16(INK4A) immunostaining on 35 biopsies with GD, 12 tubulointerstitial nephritis (TIN), and 19 normal live donor kidneys at transplantation. Based on values for 42 normal kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 25 publications
4
108
1
Order By: Relevance
“…Telomere shortening is one mechanism of senescence. Several studies reported that telomere length is decreased in patients with emphysema and COPD (32,39), consistent with chronic infection and inflammation, which induce senescence (2,21,24,30,34,35). Considering the cellular stress of recurrent exacerbations of infection and inflammation in CF, we evaluated whether CF lung airway epithelial cells also had telomere shortening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telomere shortening is one mechanism of senescence. Several studies reported that telomere length is decreased in patients with emphysema and COPD (32,39), consistent with chronic infection and inflammation, which induce senescence (2,21,24,30,34,35). Considering the cellular stress of recurrent exacerbations of infection and inflammation in CF, we evaluated whether CF lung airway epithelial cells also had telomere shortening.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation has been reported to initiate senescence in other organs including pancreas, liver, and kidney (2,21,24,30,34,35). In addition, senescent cells exhibit an inflammatory phenotype and produce inflammatory mediators including cytokines, chemokines, and metalloproteases (11,20,38,46).…”
Section: Ink4amentioning
confidence: 99%
“…Tsuji et al (2004) has shown, for example, that cigarette smoke induces senescence in alveolar epithelial cells. Sis et al (2007) used senescent-associated p16 increases instead of SA-β-Gal to detect senescent cells in kidneys with glomerular disease (GD). GDs include many conditions, which fall into two major categories: glomerulonephritis describes the inflammation of the membrane tissue in the kidney that serves as a filter, separating wastes and extra fluid from the blood; glomerulosclerosis is the scarring or hardening of the tiny blood vessels within the kidney.…”
Section: Cellular Senescence and Diseasementioning
confidence: 99%
“…[18][19][20][21][22] In experimental models, renal transplantation leads to a transient elevation in p21 CIP1/WAF1 , sustained increases of p16…”
mentioning
confidence: 99%